2018
DOI: 10.1007/s00259-018-4107-z
|View full text |Cite
|
Sign up to set email alerts
|

Region-by-region analysis of PET, MRI, and histology in en bloc-resected oligodendrogliomas reveals intra-tumoral heterogeneity

Abstract: Purpose Oligodendrogliomas are heterogeneous tumors in terms of imaging appearance, and a deeper understanding of the histopathological tumor characteristics in correlation to imaging parameters is needed. We used PET-to-MRI-to-histology coregistration with the aim of studying intra-tumoral 11 C-methionine (MET) uptake in relation to tumor perfusion and the protein expression of histological cell markers in corresponding areas. Methods Consecutive histological sections of four tumors covering the entire en blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
(92 reference statements)
3
19
0
Order By: Relevance
“…The higher the S- [ 18 F]CF 3 -D-CYS uptakes were, the higher the tumor cell proliferation was. These findings are consistent with previous reports that [ 11 C]-MET uptake correlated with the proliferative Ki67 index ( 27 29 ). On the other hand, we found that the tumor hemorrhage region, which was confirmed by SWI-MRI and histopathology, had a pretty low S- [ 18 F]CF 3 -D-CYS uptake.…”
Section: Discussionsupporting
confidence: 93%
“…The higher the S- [ 18 F]CF 3 -D-CYS uptakes were, the higher the tumor cell proliferation was. These findings are consistent with previous reports that [ 11 C]-MET uptake correlated with the proliferative Ki67 index ( 27 29 ). On the other hand, we found that the tumor hemorrhage region, which was confirmed by SWI-MRI and histopathology, had a pretty low S- [ 18 F]CF 3 -D-CYS uptake.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were confirmed by another study [49]. Subsequently, Roodakker et al [50] compared regional MET PET and PWI at 3 T with local neuropathology in patients with en bloc-resected oligodendrogliomas. They showed that MET uptake correlated with tumor cell density throughout the entire tumor volume in all patients.…”
Section: Amino Acid Pet and Pwimentioning
confidence: 63%
“…They concluded that MET PET, but not PWI, has a value as an indicator of tumor cell density in oligodendrogliomas. While in a very small study, this result differs from that of the GBM studies above and may indicate an important tumor type difference, wherein the value of PWI may be negligible for oligodendrogliomas specifically [ 39 ].…”
Section: Resultsmentioning
confidence: 81%
“…Studying these imaging modalities in oligodendrogliomas, Roodakker et al compared MET PET and PWI images acquired asynchronously, with histology as the ground truth, in four oligodendrogliomas [ 39 ]. MET PET uptake was significantly correlated to tumor cell density, but PWI was not correlated with MET PET or histology.…”
Section: Resultsmentioning
confidence: 99%